Emergency Remote Learning in the Times Of Covid: A Higher Education Innovation Strategy - Mooney, G; Duma, M; Faloye, S; Van Wyk, B (Academic Conferences and Publishing International Ltd., 2020)
Innovation in a time of crisis is not a new concept. Natural disasters and pandemics through the ages have continued to necessitate emergency adjustments on many levels, including education. Globally, the outbreaks of the COVID-19 pandemic resulted in the unexpected and wide-spread disruption of society, and in higher education. These challenges call for crisis innovation measures. The Covid-19 pandemic has forced education providers to revert to a pandemic pedagogy as a philosophy underpinning their teaching and learning strategies. The private higher education institution (PHEI) in this study has a distributed federal model, offering undergraduate and postgraduate programmes in Education, Law, Commerce, Engineering, Social Sciences and Humanities across 24 campuses. It has nearly 45 000 students in South Africa. The compulsory rolling out of the learning management system (LMS) used by the PHEI understudy across all programmes in 2014 enabled the PHEI to adapt to an emergency remote teaching model. This was done by expanding online synchronous and asynchronous learning to the rest of the programmes by employing a crisis-driven innovation strategy. This extended the blended learning approach. The emergency innovation strategy the PHEI adopted responded to this closure by adapting its existing eLearning strategy into an emergency remote teaching strategy (ERTS). This article reports on the case of a PHEI on the approach followed to adjust to this disruptive change in terms of lecturer preparation. Two important factors stood out: firstly, the need to determine the preparedness of lecturers and eTutors to teach online and remotely only; and, secondly, reaching out to students and reassuring them that their education will continue. This paper reports on the first construct.
Keywords: Emergency Remote Learning; eTeaching; Crisis-driven strategy